2020
DOI: 10.21203/rs.3.rs-60036/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultra-Processed Foods Are the Major Sources of Total Fat, Saturated and Trans-Fatty Acids Among Tunisian Preschool and School Children: A Cross-Sectional Study

Abstract: Background: Excessive intake of fat and fatty acids is associated with major health hazards such as obesity or chronic diseases. The aim of this study is to provide the first data on total fat, SFA and TFA intakes and their major food sources in Tunisian children. Methods: A total of 1200 children, aged 3 to 9 years old, were randomly selected from primary schools and kindergarten under a cross-sectional design. The 24hour recall method and food frequency questionnaire were used to assess dietary intake over a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The progress of overweight is a public health concern in Tunisia and other North African countries. Nowadays, children are exposed to a more obesogenic environment, as they tend to consume more processed and ready-to-eat food with a high content of added sugar and fat [ 41 ]. An analysis of the most consumed industrial products by children as well as fast food revealed a high amount of trans-fatty acids [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progress of overweight is a public health concern in Tunisia and other North African countries. Nowadays, children are exposed to a more obesogenic environment, as they tend to consume more processed and ready-to-eat food with a high content of added sugar and fat [ 41 ]. An analysis of the most consumed industrial products by children as well as fast food revealed a high amount of trans-fatty acids [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, children are exposed to a more obesogenic environment, as they tend to consume more processed and ready-to-eat food with a high content of added sugar and fat [ 41 ]. An analysis of the most consumed industrial products by children as well as fast food revealed a high amount of trans-fatty acids [ 41 , 42 ]. Moreover, while no official assessment of food advertisements has been conducted in Tunisia, similar countries from the Eastern and Mediterranean regions are frequently exposed to unhealthy food advertisements in mass media [ 43 ].…”
Section: Discussionmentioning
confidence: 99%